THE DEGREE OF PAIN IN THE KNEE JOINT AND ITS RELATIONSHIP TO SPEED AND AGILITY ACCORDING TO THE CODA TEST FOR FOOTBALL REFEREES - Ibrahim, Ammar Mousa; Ali, Mohammed Abdul Zahra (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
Through the field observation of the researcher as a referee for open-air football and after reviewing the sources in the field of practical specialization, does the preventive aspect of referees affect the role of tests used in special tests for football referees, and focus on the theoretical aspect of the law only? While prevention is no less important than it, and any lack of modern and advanced preventive methods will cause injury to referees, so the researcher is required to know this relationship between the CODA test for speed and agility and the degree of pain in the knee joint, and thus it will certainly lead us to the real level of referees. The aim of the research was to measure the degree of pain in the knee joint among the research sample members according to the CODA test and to identify the relationship between the CODA test for speed and agility and the degree of pain among first-class football referees. The researcher used the descriptive approach to suit the nature of the research and its field procedures and to solve its problem. The researcher defined the research community as first-class football referees (assistant referees) for the season (2023-2024). The number of them is (15) referees. As for the research sample, (10) referees were chosen randomly. After collecting the data and conducting the statistical analysis of the results, the researcher concluded that there is a significant correlation between the degree of pain and the Coda test for speed and agility, as well as the presence of simple pain among the individuals in the research sample.